Green Economy and European Politics - Mihaela MUŞAT; Elvira NICA; Maria Gabriela HORGA (Communications of International Proceedings, 2020)
Through this study we want to generate an overview of the concept of "Green Economy", considered by some specialists a solution to the problems facing all mankind. In the latest research conducted over the last 30 years, it has been found that new concepts have emerged in the global economy, concepts that start from the same premise, namely, how society will manage to create a balance between available resources, which are limited, and the needs or wishes of its members, which are potentially unlimited. Thus, currently it is pursued which of these concepts is more comprehensive, more appropriate, what similarities and differences are between them, and which will answer the best to the present and future needs of society.
Keywords: Green Economy; Development; Policies; European Union.